Peran Strategi Pemasaran dalam Meningkatkan Loyalitas dan Kepuasan Pelanggan - Azahra Khairun Nisa; Diva Nabila Millati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
Customer loyalty and satisfaction are two critical elements that greatly affect the performance and sustainability of companies in today's competitive market. This study aims to analyze the role of marketing strategies in increasing customer loyalty and satisfaction. Given that effective marketing strategies not only affect customer perceptions but can also form long-term relationships between customers and companies, it is important to understand how the strategies implemented can affect these two aspects. Through this study, we explored various marketing strategy components such as market segmentation, targeting, brand positioning, and relationship marketing, and how they contribute to achieving customer satisfaction and loyalty. The results show that an integrated marketing strategy that focuses on customer needs and wants significantly increases customer satisfaction, which in turn strengthens their loyalty. Using quantitative analysis methods through surveys and linear regression, this study provides empirical insights into the relationship between marketing strategies and customer satisfaction and loyalty, as well as implications for marketing practices in various industry sectors.